GEOCHEMICAL CHARACTERIZATION OF GROUNDWATER FROM HARD ROCK TERRAIN OF CHEYYAR TALUK, THIRUVANNAMALAI DISTRICT, SOUTH INDIA - Senthilkumar, S.; Vinodh, K.; Gowtham, B.; Suresh, V.M. (My University, 2019)
Cheyyar Taluks forms part of Thiruvannamalai District, covering an area of 634 sq.km and lies in the northern part of Tamilnadu. This study area covers three administrative blocks named as Cheyyar, Vembakkam and Anakkavur. Study area is bounded by the Kancheepuram and Arakkonam Taluk in the North and Utthiramerur Taluk in the East and Arcot Taluk in the West and Vandavasi Taluk in the South. The study area total population is 380,367 as per 2011 census. Cheyyar Taluk lies between 120 52’55’’N to 120 32’52”N Latitude and 790 19’02’’E to 790 44’42’’E longitudes. The area constitutes a part of Toposheet Nos. 57P/6, 9, 10, 13 and 57P/14 published by Survey of India. The chief irrigation sources in the area are the tanks, and dugwells and tube wells. The study area is studded with numerous surface water storage tanks of medium and minor types. Rural population is mainly engaged in agriculture in the surveyed area. Paddy and Sugarcane is the major food crop in the area and it is extensively cultivated (two crops) in entire Taluk. The drainage pattern is generally dendritic. All the rivers are seasonal and carry substantial flows during monsoon period. The study area includes part of Palar and Cheyyar river basin. The study area depends on surface and rainwater for domestic and irrigation purposes. The geology of the area constituted by Charnockites of Archeaen age, Epidote- hornblende Gneiss and Hornblende-Biotite Gneiss with Sand, silt ang Graval of sedimentary rocks. The predominant Geomorphologic feature in the study area is pediments, shallow pediments, flood plains, buried pediments, Sedimentary low land, Denudation hills and river basin. Around 25 representative ground water samples were collected and they are physico-chemically analysed. The pH of the groundwater is Basic to Acidic in nature. With reference to TH, the majority of the groundwater sample locations in Cheyyar Taluk are very hard water with little hard to moderately hard water. In comparison with Bureau of Indian Standard (BIS, 1983) for drinking water the majority of the ground water samples in the study area falls above the maximum permissible limit on the basis of TDS and TH. Thus the effect of groundwater on the health of livestock’s and human population are discussed in detail for the various ground water chemical parameters.
Keywords: ground water, geochemical, effect of ground water